(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article talks about the aspects that should be paid attention to when preparing a portrait longride, which is becoming popular today in foreign Internet publications, the main stages of creating material in this format, and the possibilities of multimedia platforms.